Evaluasi Kualitas Benih Padi Junjuang (Varietas Unggul Lokal) dengan Aplikasi Pupuk Organik KoHeA+MF - Wulantika, Trisia; Fitri, Febria; Sondang, Yun; Hardaningsih, Wiwik; Wahono, Sentot (Universitas Medan Area, 2025)
Rice is a primary commodity in the national food security system; however, challenges such as low seed quality and the use of environmentally unfriendly chemical fertilizers continue to limit productivity. This study aims to evaluate the seed quality of Junjuang rice, a superior local variety from West Sumatra, cultivated using the organic fertilizer KoHeA+MF (a combination of chicken manure and banana corm MOL). The research was conducted descriptively at the Seed Technology and Plant Propagation Laboratory, Politeknik Pertanian Negeri Payakumbuh, over a two-month period (January–February 2024). Seed quality parameters analyzed included 1000-grain weight, moisture content, seed purity, and germination rate. The results showed that Junjuang rice seeds had a 1000-grain weight of 18.776 grams, purity of 96.08%, germination rate of 98.2%, and an average moisture content of 13.08%, all within the acceptable range of national seed quality standards. The application of KoHeA+MF organic fertilizer significantly contributed to the improvement of both physical and physiological seed qualities, through enhanced soil conditions and nutrient availability for the mother plants. These findings indicate that the use of KoHeA+MF organic fertilizer can serve as an effective strategy for improving the quality of local rice varieties and supporting sustainable agriculture in the region.